Instagram Sebagai Media Branding Institusi Untuk Mempersuasi Gen Z Dalam Memilih Pendidikan Tinggi - Dewi, Danar Kristiana; Budiwati, Yulia (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to describe how social media is a digital branding tool that is very effective in inviting Generation Z to choose higher education. This research uses qualitative research methods, which are presented descriptively. Data sources for this research will be obtained in two categories, namely primary data sources and secondary data sources. Primary data sources were obtained from Instagram @utsurakarta. Meanwhile, secondary data sources were obtained from literature in the form of data, results of previous research, books, archival journals and interviews. The results of the research show that the methods used by UT Surakarta in branding itself as the campus of choice for Generation Z through social media are quite varied. Strengthening the UT brand is done visually by choosing consistent colors in each post. Then, the selection of charm buyers or figures in the content is also interesting and represents the target market segment.